ANALISIS PENINGKATAN EKONOMI MASYARAKAT DI AGROWISATA BELIMBING KARANGSARI KOTA BLITAR - Erika Nur Aida; Arfida Boedirochminarni; Ida Nuraini (Jurnal Ilmu Ekonomi JIE, 2017)
Kelurahan Karangsari after established of Karangsari Starfruit Agrotourism in Blitar City we can see economic development in society with how Starfruit farmer’s income transformed. For knowing income differentiation of Starfruit farmer we use paired sample t-test method. This research found that after established of Karangsari Starfruit Agrotourism in Blitar City give positive influence for Starfruit farmer. The influence is the increasing demand for the product, the creation of product quantity, the creation of selling price, the creation of product innovation, and give more employment opportunity for society who live nearby. The creation Starfruit farmer income in a significant way show that there is differentiation after established Karangsari Starfruit Agrotourism in Blitar City.Keywords: Agrotourism, Karangsari Starfruit, Blitar City, Farmer’s  Income, And Paired Sample T-Test.